The Warrior State : Pakistan in the Contemporary World - Paul, T. V. (Karachi Oxford University Press, 2014)
In The Warrior State, noted international relations and South Asia scholar T.V. Paul untangles this fascinating riddle. Paul argues that the "geostrategic curse"--Akin to the "resource curse" that plagues oil-rich autocracies--is at the root of Pakistan's unique inability to progress. Since its founding in 1947, Pakistan has been at the center of major geopolitical struggles: the US-Soviet rivalry, the conflict with India, and most recently the post 9/11 wars. No matter how ineffective the regime is, massive foreign aid keeps pouring in from major powers and their allies with a stake in the region. The reliability of such aid defuses any pressure on political elites to launch the far-reaching domestic reforms necessary to promote sustained growth, higher standards of living, and more stable democratic institutions. Paul shows that excessive war-making efforts have drained Pakistan's limited economic resources without making the country safer or more stable. Indeed, despite the regime's emphasis on security, the country continues to be beset by widespread violence and terrorism.
Include maps, notes and index.
Pakistan in the contemporary world as the warrior state
Keywords: War--Economic aspects -- Pakistan -- Politics and government -- National security -- Economic development -- Geopolitics